INFLUENCE OF SIZE AND NUMBER OF NACA 0012 BLADES ON THE MECHANICAL POWER OF WIND TURBINE-POWERED CAR - Moktar A. Hashem Mohamad; Youssef Kassem (International Journal of Innovations in Engineering Research and Technology, 2023)
The vertical axis wind turbine (VAWT) can harness wind energy. However, there are still significant gaps in our understanding of VAWT aerodynamics and performance, particularly when it comes to designing and selecting blade chords and height. In the case of a wind car, it utilizes a vertical axis and employs a varying number of NACA 0012 blades positioned at a 2° angle of attack and mounted at different angles. These blades are directly connected to wheels using various mechanisms, while gears are used to convert wind energy into mechanical energy to overcome the load on the main shaft during low speeds. The objective of this study is to investigate the influence of blade number and size on the mechanical power of the rotor. Specifically, we measured the torque and mechanical power acting on a blade at an airflow speed of 4 m/s and an angular velocity of 13.056 rad/s, based on previous scientific research.